Evaluation of the sensory quality of monofloral honey - Estevinho, Leticia M. (2013)
Honey is an alimentary product much appreciated due to his aroma, flavor and nutritional characteristics. The sensorial analysis is important in the evaluation of the quality and authenticity of monofloral honeys. It considers attributes as color, aroma, consistence and flavor, which are interlinked and depend on the volatile compounds related with the fragrance of the flowers where the nectar was collected. The aroma and the flavor are also related directly with honeys’ color. The objective of this work was to evaluate the pollinic profile and the sensorial characteristics of four honeys from biological mode of production. The pollen analysis indicated that all of the analyzed honeys were monofloral,presenting as dominant pollen Lavandula sp. (45.83%), Erica sp. (49.69%), Prunus sp. (61.91%) and Castanea sp. (69.01%). The results obtained in the sensorial analysis performed by the consumer’s panel were treated by the Generalized Procrustes method. It was verified that the attributes that the consumers managed to evaluate more easily and whose contribution for the global appreciation was more accentuated were the color, the flavor and the consistence. The cherry tree honey presented higher values in the scale of preferences in terms of global appreciation, color, flavor, consistence and intermediate values regarding the aroma. Concerning the heather honey, aroma was the most valued attribute. Honeys from chestnut and rosemary were the ones that received lowest punctuation.